About the concept of "Zhaksy Kazakh" by academician GarifollaYesim (Journal of Philosophy Culture and Political Science, 2022)
Over the past decades, our country has implemented many events and strategic programs dedicated to the revival of cultural and spiritual values, national traditions and customs. Achievements such as the organization and holding of various landmark meetings, summits, kurultays, forums, congresses, the World EXPO Exhibition, world-class sports competitions or discoveries made by domestic scientists contribute to raising the status and authority of the country on the world stage. These achievements, in turn, testify to the active spiritual life of the country. It would not be an exaggeration to say that the impetus is given by scientists and intellectuals working in the humanitarian field, who not only generously share their knowledge with students of higher educational institutions of the country, but also consistently discuss issues related to the future of the country, offering their constructive proposals.One of such outstanding scientists-innovators can be called Professor of the Department of Philosophy of the L. N. Gumilev Eurasian National University, Academician of the National Academy of Sciences of the Republic of Kazakhstan Garifolla Yessim. Having structured and systematized the creative searches and ideas that he had been thinking about all his life, he created the author's philosophical concept "Zhaksy Kazak", directly related to the national idea "Mangilik El". The purpose of this article is to reveal the essence and content of the concept of Academician Garifolla Yessim. The core center of the theory is the category "Zhaksy Kazak", considered from an image position, and seven stages of its achievement (advantage (daulet), enterprise, tradition, the idea of "Kazak kyzy", continuity, new innovative thinking, "Zhaksy kazak)). It should be said that these seven stages have been worked out in the educational and methodological plan and are studied within the framework of the educational programs "Philosophy", "Cultural Studies" as elective disciplines The practical significance of the concept lies in the fact that certain aspects of it have become the subject of research of the academician's students at the level of doctoral dissertations, the successful defense of which indicates the relevance of ideas a scientist.Keywords: philosophy, culture, idea, concept, system, creativity, discipline.